Discovery on Beal Conjecture - Bado, Idriss, Olivier (My University, 2019)
In this paper we give a proof for Beal's conjecture . Since the discovery of the proof of Fermat's last theorem by Andre Wiles, several questions arise on the correctness of Beal's conjecture. By using a very rigorous method we come to the proof.
Keywords: Lemma; Theorem; Beal; Fermat; Conjecture